Population aging, labor demand, and the structure of wages - Michael Papadopoulos; Margarita Patria; Robert K. Triest (Federal Reserve Bank of Boston, 2017)
One consequence of demographic change is substantial shifts in the age distribution of the workingage population. As the baby boom generation ages, the usual historical pattern of a high ratio of younger workers relative to older workers has been replaced by a pattern of roughly equal percentages of workers of different ages. One might expect that the increasing relative supply of older workers would lower the wage premium paid for older, more experienced workers. This paper provides strong empirical support for this hypothesis. Econometric estimates imply that the size of one's birth cohort affects wages throughout one's working life, with members of relatively large cohorts (at all stages of their careers) earning a significantly lower wage than members of smaller cohorts. Estimated elasticities of wages with respect to the relative size of one's own cohort are generally between -0.05 and -0.10, and are of similar magnitude for men and for women. Our results suggest that cohort size effects are quantitatively important and should be incorporated into public policy analyses.
Keywords: J11; J21; J26; 330; labor market demographics; population aging; wage structure; social insurance